Early On-Treatment Nutritional Change and Baseline Inflammation Stratify Outcomes in Patients Receiving Immune Checkpoint Inhibitors - Doğan, Tolga; Demiray, Atike Gökçen; Yapar Taşköylü, Burcu; Hafızoğlu, Emre; Yaren, Arzu; Gököz Doğu, Gamze (The European Research Journal, 2026)
Objectives: In patients receiving immune checkpoint inhibitors (ICIs), baseline nutritional status is frequently recorded, but what happens during treatment may be at least as informative. We examined whether the 3-month change in Mini Nutritional Assessment (ΔMNA)–Short Form (SF) is associated with survival, and how this relates to baseline systemic inflammation measured by modified Glasgow Prognostic Score (mGPS). Methods: We retrospectively screened institutional records and included 54 adults with advanced/metastatic solid tumors treated with ICIs who had MNA-SF documented at treatment start and again at approximately 3 months. ΔMNA was defined as MNA-SF (~3 months) minus baseline MNA-SF (higher values indicate improvement) and was categorized for Kaplan–Meier analyses as worsened (≤ −1), stable (= 0), or improved (≥ +1). Baseline mGPS was derived using CRP >5 mg/L and albumin